Benefit-cost Analysis - a Possibly Overemphasized Criteria in Forestation Evaluations - Pant, M. M. (Indian Forester, 1975)
The benefit cost analysis is an useful tool in providing the correct investment criterion for evaluating projects. However, it is a possibly overemphasized criteria. There are countless positive externalities such as soil and water conservation, aesthetic values, etc., which are generated by the forest. These should also be accounted for any realistic evaluation. It may be necessary to lay out a set of "Central Guide Lines" regarding the procedure to be followed on the National Basis for the evaluation of costs and Benefits involved in forestry project. However, economic efficiency is to be less interest-ing if the object of forestation is to serve the regional scarcity and to achieve self sufficiency.